KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH UNTUK MEWUJUDKAN INOVASI SEKOLAH DI SMKN 2 BUDURAN SIDOARJO - Nesha Aisyah; Erny Roesminingsih (STKIP Pesisir Selatan, 2026)
This article aims to describe the principal's transformational leadership practices in fostering school innovation at SMKN 2 Buduran Sidoarjo. The study employs a qualitative approach with a single-case study design. Data were gathered through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using the Miles-Huberman interactive model. The results indicate that the principal's transformational leadership is manifested through four key dimensions: leading by example, communicating innovation, encouraging teacher involvement, and mentoring the school community to realize their potential. Leading by example is reflected in the principal's discipline, direct involvement in school activities, and consistency between words and actions. Communication is facilitated through meetings, briefings, digital media, and participatory forums to ensure the entire school community understands the direction of school development. The principal also fosters teacher involvement through training, recognition, opportunities for innovation, and cross-disciplinary collaboration. Furthermore, continuous mentoring is provided to teachers and students to cultivate their potential, creativity, and achievements. The findings demonstrate that transformational leadership plays a pivotal role in building an innovative culture, strengthening collaboration among the school community, and realizing the